Renew the evaluation and ranking trade union organization - THỊ HÀVŨ (Tạp chí Nghiên cứu Khoa học Công đoàn, 2018)
In trade unions activities, evaluation and ranking at all levels organization are very necessary. This is not only thebasis for the performance of the emulation movements of the General Confederation, the reward for trade unions at all levels, butalso the basis for propaganda and mobilization at all levels of the union to improve the quality of activities through compliance andachievement of predetermined evaluation criteria. Evaluation and ranking of trade unions are also in line with regulations of theCentral Organization Committee on the review, evaluation and ranking of the quality of activities of organizations and individuals;it is in line with the general tendency of Vietnam’s political and social organizations. The evaluation and ranking of trade unions in thepast years is still inadequate due to various reasons. Therefore, the renewal of the evaluation and classification of trade unions is verynecessary.